Addressing the decline in the accounting talent pipeline - Mohd Sofi, Nurin Jazlina; Che Hassan, Anita (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The accounting profession is currently experiencing a decline in talent, with fewer students pursuing accounting degrees and an increasing number of professionals leaving the field. This trend poses significant challenges for businesses, regulatory bodies, and financial institutions, as accountants play a critical role in financial reporting, tax compliance, auditing, and strategic decision-making. This paper examines the key factors contributing to the talent shortage, including technological disruption, work-life balance concerns, salary competitiveness, and educational gaps. The literature review explores the evolving role of accountants, the impact of automation and artificial intelligence, and the misalignment between academic curricula and industry needs. The discussion highlights the challenges faced by the profession, emphasizing the need for adaptability and innovation. To address these issues, the paper recommends the implementation of mentorship programs, flexible work arrangements, competitive compensation packages, and enhanced career growth opportunities. By adopting these strategies, the accounting profession can attract and retain skilled professionals, ensuring its sustainability in an increasingly digital and dynamic business environment.